Politics and public protection - Nash, Mike; Williams, Andy (Emerald advances in historical criminology., 2024)
Sitting at the extreme end of criminal justice and offending behaviour, public protection policy has been politicised and used to reshape wider debates. Exploring the development of public protection policy and legislation since the early 1990s, Politics and Public Protection considers the necessity for extreme measures and the actual extent of serious crime to unveil the populist nature of the way political debates have been framed over time. Analysing the UK setting where the public protection debate has been 'weaponised' to create public fear and 'with us or against us' positions, authors Mike Nash and Andy Williams chronicle how this form of politics has now extended into a range of policy areas, including Brexit. Emphasising the political context of the evolution of public protection policy over time, the chapters investigate different types of dangerous criminal behaviour, public protection agencies and responses to panic and failure, providing a critical analysis of the use of risk to reshape and reframe public protection policy and practice. Responding to the need for an updated discussion on public protection and criminal justice legislation that links the past to the present, Politics and Public Protection closely examines the interplay between politics and extreme criminal justice measures.